Immunotherapy at any line of treatment improves survival in patients with advanced metastatic non‐small cell lung cancer (NSCLC) compared with chemotherapy (Quijote‐CLICaP) (2020)
Background: To compare survival outcomes of patients with advanced or metastatic non-small cell lung cancer (NSCLC) who received immunotherapy as first-, second- or beyond line, versus matched patients receiving standard chemotherapy with special characterization of hyperprogressors. Methods: A retrospective cohort study of 296 patients with unresectable/metastatic NSCLC treated with either, first-, second-, third- or fourth-line of immunotherapy was conducted. A matched comparison with a historical cohort of first-line chemotherapy and a random forest tree analysis to characterize hyperprogressors was conducted. Results: Median age was 64 years (range 34–90), 40.2% of patients were female. A total of 91.2% of patients had an Eastern Cooperative Oncology Group (ECOG) performance score ≤ 1. Immunotherapy as first-line was given to 39 patients (13.7%), second-line to 140 (48.8%), and as third-line and beyond to 108 (37.6%). Median overall survival was 12.7 months (95% CI 9.67–14 months) and progression-free survival (PFS) of 4.27 months (95% CI 3.97–5.0). Factors associated with increased survival included treatment with immunotherapy as first-line (P < 0.001), type of response (P < 0.001) and PD-L1 status (P = 0.0039). Compared with the historical cohort, immunotherapy proved to be superior in terms of OS (P = 0.05) but not PFS (P = 0.2). A total of 44 hyperprogressors were documented (19.8%, [95% CI 14.5–25.1%]). Leukocyte count over 5.300 cells/dL was present in both hyperprogressors and long-term responders. Conclusions: Patients who receive immune-checkpoint inhibitors as part of their treatment for NSCLC have better overall survival (OS) compared with matched patients treated with standard chemotherapy, regardless of the line of treatment.